Study on the inclusion of two microstrip square open loop resonator to produce a diplexer / Nor Azzahra Ibrahim - Ibrahim, Nor Azzahra (2015)
In this paper, a microstrip square open loop resonator as one of the design for band pass filter is proposed to develop the diplexer. A combination of two microstrip open loop resonator connected to power divider (assume to be ideal power divider) will produce a diplexer. The microstrip square open loop resonator is one of the bandpass filter type of filter operating at two frequencies, GSM1800 MHz and UMTS2150 MHz. Comparisons between simulated and measured result shows a shifting in return loss, Sn and insertion loss, S21. From the results, simulated result shows a better return loss and insertion loss. Expected result for diplexer should be the same as the microstrip square open loop resonator since the diplexer is form from the inclusion of two microstrip square open loop resonator. By having this diplexer in the telecommunication, it can overcome many issue as for example on the public complaint regarding radiation from the base station. As for operator itself, they can reduce the OPEX and CAPEX cost.